Expanding Assessments of Translational Research Programs: Supplementing Metrics With Value Judgments. (March 2014) - Scott, Craig S.; Nagasawa, Pamela R.; Abernethy, Neil F.; Ramsey, Bonnie W.; Martin, Paul J.; Hacker, Beth M.; Schwartz, Havivah D.; Brock, Douglas M.; Robins, Lynn S.; Wolf, Fred M.; Carter-Dubois, Marie; Disis, Mary L.
The University of Washington (UW) Institute for Translational Health Sciences (ITHS), funded by a Clinical and Translational Sciences Award program, has supplemented its initial Kellogg Logic Model–based program evaluation with the eight judgment-based evaluative elements of the World Health Organization's (WHO) Health Services Assessment Model. This article describes the relationship between the two models, the rationale for the decision to supplement the evaluation with WHO evaluative elements, the value-added results of the WHO evaluative elements, and plans for further developing the WHO assessments.